Pendidikan Kesehatan Dan Pemberian Tablet Zat Besi (Fe) Dalam Upaya Meningkatkan Kadar Hemoglobin Ibu Hamil - Ekawati, Nur; Srifitayani, Nur Rahma; Fitri, Lidia; Hasibuan, Evis Ritawani; Anurogo, Dito; Harfika, Meiana; Hijrah, Hijrah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Various efforts have been made by the Ministry of Health to overcome anemia in pregnant women, including routine provision of iron tablets to pregnant women. This coverage has not reached the national standard of 90%, so efforts need to be made to achieve the set target. The factors causing the failure to achieve the target of the Fe supplementation program are not yet known. One of the nutritional problems that often occurs in pregnant women is nutritional anemia, which is the largest and most difficult micronutrient problem to overcome worldwide. The purpose of PkM is to overcome the incidence of anemia in pregnant women so that it is necessary to organize and manage the provision of iron tablets. The methods used in PkM activities are health education and provision of iron (Fe) tablets in an effort to increase hemoglobin levels in pregnant women using interviews, questions and answers and questionnaires. The results of this community service activity are that all pregnant women in the Malino Health Center work area understand and want to take Fe tablets, so that it can reduce the incidence of anemia in this area. The conclusion of this activity is that there is an effect of providing Fe tablets on increasing Hb levels in pregnant women in the Malino Health Center work area with a pvalue = 0.000 with a 2 mean value of 1.6152.